The influence of upper- and lower-body maximum strength on swim block start, turn, and overall swim performance in sprint swimming - Keiner, M.; Wirth, K.; Fuhrmann, S.; Kunz, M.; Hartmann, H.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2021)
Maximum strength and speed strength are 2 major factors that determine a swimmer's performance, including swim start and turn performance, which directly impacts overall swim sprint performance. Nevertheless, data regarding the relationship between swimming performance and maximum strength are not consistent. Specifically, there are minimal data examining the relationship between maximal strength levels, start and turn performances in the scientific literature. This study was designed to determine the relationship between strength and specific markers of swim performance. Therefore, 14 moderate trained swimmers (male; 17.5 ± 1.6 years; mass: 70.2 ± 4.8 kg; height: 181.9 ± 5.7 cm) were tested for maximum strength in back squat and bench press, squat and countermovement jump performance, tethered swimming and swim performance (50- and 100-m crawl sprint, where start and turn performances were also analyzed). A multiple regression analysis was performed using the maximum strength data as predictors of 15-m start performance and swimming power. Furthermore, bivariate Pearson correlation analyses were used to assess the relationship between the strength and power variables and the swim variables. Maximum strength in the bench press and squat explained 50-65% of the performance variance in swimming power and start performance and 45-62% of the performance variance in 50-/100-m swimming performance. The results of this study demonstrated that maximum strength of the upper and lower limbs and jump height were strongly related to sprint swim performance. Therefore, maximum strength in squat and bench press should be included in strength tests, and that swimmers should incorporate lower- and upper-body strength and power training into their training schedule.